Efektivitas Kedudukan Direksi sebagai Personal Guarantee dalam Hal Kepailitan Perseroan Dikaitkan dengan Pembuktian Sederhana : Studi Kasus Putusan No. 20/Pdt.Sus-Pailit/2022.PN.Niaga.Smg - Rifasya Naura Salsabila; Etty Mulyati; Nun Harrieti (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
One of the organs of a Limited Liability Company that often becomes a guarantor of a company’s debt is the Board of Directors. In practice, when a company can no longer carry out its obligations to pay debts, the guarantor is often bankrupted together with the debtor. Article 2 paragraph (1) jo. Article 8 paragraph (4) of the Bankruptcy and PKPU Law states that if the Debtor has two or more Creditors and has debts that are due and collectible, then the request for a bankruptcy statement must be granted if there are facts or circumstances that are proven simply. This research was conducted to examine the legal considerations of judges regarding the application of simple proof in Decision Number 20/Pdt.Sus-Bankruptcy/2022/PN.Niaga.Smg and what the implications are for the Directors of the company who act as a personal guarantee for their company’s debt. The results showed that the legal consideration of the majority of the Panel of Judges examining the case are not entirely in accordance with the Bankruptcy and PKPU Law, as the panel of judges only focused on fulfilling formal requirements without considering the principles of bankruptcy, which will have a broad impact on the parties involved. In addition, the juridical implications arising from the decision are that the Directors of the company as a personal guarantee remains personally responsible for the company’s debt, thus causing bankruptcy for him and the company.